On-farm research and transfer of technology for cassava production in Vietnam - Hoang, Kim; Tran, Van Son; Nguyen, Van Thang; Tran, Ngoc Quyen; Ao, Van Thinh (International Center for Tropical Agriculture, 1995)
In Vietnam, extension activities are considered by the government as an urgent and longterm measure, that has a great influence on the production process of farmer commodity production. Among extension objectives, cassava production is given great importance in those areas where appropriate conditions for its development exist. This paper presents an overview of the extension strategy, structure and organization in Vietnam, the linkage of national cassava research and extension organizations, and the objectives and methods of extension activities in Vietnam. This paper also analyzes in detail the results of on-farm research and transfer of technology for cassava production conducted by the Hung Loc Agricultural Research Center. Among the initial achievements is the release of cassava varieties HL-20, HL-23 and HL-24, which are now grown in thousands of hectares every year. A cultural technique of intercropping cassava with mungbean, peanut and winged bean has obtained satisfactory results, contributing to increased farmer income and the maintainance of soil fertility. Cassava germplasm introduced from the Thai-CIAT program is very promising, in particular Rayong 60. This variety is now released by MAFI for multi-locational field trials and dissemination in production fields. A research and extension network for cassava production in Vietnam has been established by linking the National Food Crops Program with the National Extension Program with the support of international organizations such as CIAT, CIP and IDRC. Through this network, new cassava varieties and advanced cultural techniques will be transferred to production fields very quickly